The SNP CYP2C19*2 (rs4244285) genotyping using tetra primer arms PCR method - Rupoma, Afia Adiba (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.